Production and social factors of economy - L. A. Akhmetov; D. A. Zuravlev (Путеводитель предпринимателя, 2020)
In article problems and questions of acceleration of growth of national economy, factors on ensuring increase of really located income of citizens of the country, decrease in level of poverty, realization of achievements of scientific and technical progress (the fourth industrial (industrial) revolution), implementation of some national projects are considered.